Sandman to Sandman: A Parody Into Madness - Irwin, Rey; Gudenkauf, Eric (My University, 2017)
This is a parody of the song Mr. Sandman by the Chordettes based on the short story “Der Sandman” written by E.T.A Hoffmann in 1816. We chose to utilize a musical format as music is a language people can understand whether or not they understand the language. The first verse talks about the death of Nathaniel’s father, the second verse talks about his infatuation with Olympia, and the third verse is his final descent into madness ending with the words “Skone Oke.” Parodies are able to accomplish the goals of poking fun at the source material while simultaneously summarizing the story in a concise manner. Creating a song parody managed to explain the major themes of the story and examine Nathaniel’s descent into madness in a comedic way that a paper written on this subject would not have been able to accomplish.
Citation: Irwin, R., & Gudenkauf, E. (2017). Sandman to Sandman: A Parody Into Madness. Initials: Student Research Forum, April 21, 2017. Manhattan, KS.
Keywords: Der Sandmann; E.T.A. Hoffmann; German Literature; Parody; Madness; Music